Increased spontaneous physical activity in female MEST-deficient mice protects against diet-induced obesity - Anunciado-Koza, Rea Victoria P.; Martinez, M. Elena; DeMambro, Victoria; Hernandez, Arturo; Koza, Robert A. (Frontiers in Endocrinology, 2025)
IntroductionMesoderm-specific transcript (Mest), a paternally expressed imprinted gene, is involved in the modulation of adipose tissue expansion. Mest is also highly expressed in the developing and adult brain, suggesting a role in behavioral phenotypes. Previously, we showed that female mice with paternal Mest inactivation (MestpKO) exhibit no discernible behavioral impairments compared to wild-type mice. In this study, we performed metabolic phenotyping of female MestpKO mice in response to a dietary challenge.MethodsEight-week-old female and male wild-type and MestpKO mice were fed a control or Western diet (40 kcal% fat) until 24 weeks of age. Body weight, body composition, and metabolic parameters were measured during the course of the feeding regimens, and gene expression and type-2-deiodinase (DIO2) activity were examined in white adipose tissue and brain at the end of the study.ResultsMestpKO female mice fed a Western diet were protected against diet-induced obesity. Strikingly, these mice showed increased ambulatory activity and speed, coupled with reduced resting parameters, suggesting a role for MEST in the regulation of spontaneous physical activity, a form of nonexercise activity thermogenesis. When considering body mass (control diet) and lean mass (Western diet), energy expenditure was increased in the female MestpKO mice. Male MestpKO mice did not exhibit these changes. Analyses of hypothalamic gene expression revealed upregulation of Dio2, and RNA-seq highlighted differential expression of numerous thyroid hormone-responsive genes in MestpKO female mice.ConclusionMechanistically, our results suggest that MEST directly or indirectly regulates thyroid hormone-responsive genes in the hypothalamus, thereby modulating the neurobiological control of nonexercise activity thermogenesis in Western diet-fed female mice.